Adaptations to drought: evidence from ag producer survey - Pritchett, James, author; Goemans, Christopher, author; Nelson, Ron, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2013)
Colorado's ongoing drought is in its significant geographic reach and economic impacts. For Ncondition, reduces cow condition and leads to difficulty in locating critical feed inputs. These production losses generally reduce revenues although declining receipts may be partially offset by higher prices. Yet, the drought's impacts to the farm or ranch business are not contained within a single season. Much like reservoir levels that are drawn down and may take years to replenish, the impact of a drought can reduce a farm or ranch's equity position making it difficult to service debt or take advantage of future investment opportunities. Equity erosion may take years to rebuild. In this article, recent drought survey responses are described in order to characterize the potential longer term impacts of drought. Emphasis is placed on production losses and producers' mitigating actions. While it is difficult to forecast the length of the recovery period for Colorado farmers and ranchers, their adaptations and changing production activities in 2012 do indicate the severity and persistence of financial stress.
July 2013.
Keywords: debt; assets; crop yields; Colorado; economic conditions; cow-calf production; drought